2023
DOI: 10.3390/metabo13020155
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Mass Spectrometry in Salivary Metabolomics and Proteomics

Abstract: The metabolomics and proteomics analysis of saliva, an excellent biofluid that is a rich source of biological compounds, allows for the safe and frequent screening of drugs, their metabolites, and molecular biomarkers of various diseases. One of the most frequently used analytical methods in saliva analysis is liquid chromatography coupled with mass spectrometry (LC-MS) and tandem mass spectrometry. The low ionisation efficiency of some compounds and a complex matrix makes their identification by MS difficult.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 161 publications
1
0
0
Order By: Relevance
“…However, 15.3% of DEPs (cluster 2) were only increased in mild/moderate periodontitis, while 1.5% of proteins were only altered in severe (cluster 9) or aggressive (clusters 3 and 4) periodontitis. Previous studies have reported alterations in saliva proteins such as DMBT1, mucin 5B, mucin 7, lactoferrin, and MMP-8 in periodontal diseases. Recently, it was reported that matrix metalloproteinase-9 (MMP-9), S100A8, α-1-acid glycoprotein (A1AGP), and pyruvate kinase could differentiate health from gingivitis and periodontitis, and mild to moderate from advanced periodontitis . Our study displayed the gradual increase of salivary MMP-8, S100A8, and pyruvate kinase (cluster 5) from mild/moderate to severe and aggressive periodontitis, while DMBT1, mucin 5B, and mucin 7 (cluster 8) were equally decreased in these three types of periodontitis.…”
Section: Discussionsupporting
confidence: 53%
“…However, 15.3% of DEPs (cluster 2) were only increased in mild/moderate periodontitis, while 1.5% of proteins were only altered in severe (cluster 9) or aggressive (clusters 3 and 4) periodontitis. Previous studies have reported alterations in saliva proteins such as DMBT1, mucin 5B, mucin 7, lactoferrin, and MMP-8 in periodontal diseases. Recently, it was reported that matrix metalloproteinase-9 (MMP-9), S100A8, α-1-acid glycoprotein (A1AGP), and pyruvate kinase could differentiate health from gingivitis and periodontitis, and mild to moderate from advanced periodontitis . Our study displayed the gradual increase of salivary MMP-8, S100A8, and pyruvate kinase (cluster 5) from mild/moderate to severe and aggressive periodontitis, while DMBT1, mucin 5B, and mucin 7 (cluster 8) were equally decreased in these three types of periodontitis.…”
Section: Discussionsupporting
confidence: 53%